Komposisi, Kemelimpahan dan Keanekaragaman Fitoplankton Danau Rawa Pening Kabupaten Semarang - Samudra, Sesilia Rani; Soeprobowati, Tri Retnaningsih; Izzati, Munifatul (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Rawa Pening is a semi natural lake which is utilized for hydro-electric power plant, caged fish culture, irrigation, and tourism. It belongs to one of the fifteen lakes which receives national priority to be saved and preserved because of its very poor condition as a result of eutrophication, sedimentation and degraded water quality. Eutrophication of Rawa Pening comes from the Water Catchment Area, originating from farms, animal husbandry, domestic and industrial waste around the lake, and also from the water body itself, that is from caged fish culture. The fertility criteria of the lake water can be determined on the basis of the abundance and variety of phytoplankton and the total phosphorus content. The aim of this research is to find out the water fertility criteria of Lake Rawa Pening based on the abundance and variety of phytoplankton, and the phosphorus content. Research began in July 2012 on three stations. Station I is an area with fishcage culture; Station II is an area without fishcage culture, and Station III is the river inlet or water catchment area. Each station consisted of three different sampling areas. The phytoplankton abundance at the station without fishcage culture is higher (19012 ind/l) than at the fishcage culture station (14356 ind/l) as well as at the inlet station (11058 ind/l), but the diversity index at the no fishcage station is lowest (1.80) compared to the fishcage culture station (2.32) and the inlet station (2.05). The fertility criteria of Rawa Pening based on the phytoplankton abundance and P-total of its water is eutrophic going towards hypereutrophic. Keywords : Lake Rawa Pening, Phosphorus, Water Quality, Euthropication